Effect of Colchicine Treatment on Clinical Course in Children with PFAPA Syndrome - Bagrul, İlknur; Aydin, Elif Arslanoglu; Tuncez, Serife; Baglan, Esra; Özdel, Semanur; Bülbül, Mehmet (Klinische Pädiatrie, 2024)
Introduction Periodic fever, aphthous stomatitis, pharyngitis, and cervical adenitis syndrome (PFAPA) is the most common periodic fever condition in children. There is no consensus on treatment to prevent attacks and reduce their frequency. In this study, we aimed to evaluate the effectiveness of colchicine treatment in PFAPA syndrome. In addition, we described the demographic and clinical features of PFAPA patients.Materials and Methods We retrospectively analyzed 58 PFAPA patients who were started on colchicine treatment between January 2017 and January 2022. Demographic data, clinical features, laboratory tests, genetic analysis of MEditerranean FeVer (MEFV) mutations, and autoinflammatory disease activity index (AIDAI) scores of all patients were evaluated. In addition, patients were divided into two groups according to MEFV variants and compared.Results Attack frequency, duration, and AIDAI scores decreased in all patients after colchicine treatment. Duration of follow-up was 13.53±6.65 months. The median±IQR age at diagnosis was 3.2 (2–5) years. Thirty three (56.9%) patients had heterozygous mutations of MEFV. The most common MEFV variants were M694V (63.6%). There was no significant difference between the two groups in terms of colchicine responses.Conclusion Colchicine treatment is effective and safe in patients with PFAPA who have frequent attacks. No association was established between the presence of heterozygous mutations of MEFV and colchicine response.Einführung Periodisches Fieber, aphthöse Stomatitis, Pharyngitis und zervikales Adenitis-Syndrom (PFAPA) ist die häufigste periodische Fiebererkrankung bei Kindern. Es besteht kein Konsens über die Behandlung, um Anfällen vorzubeugen und ihre Häufigkeit zu verringern. In dieser Studie wollten wir die Wirksamkeit der Colchicin-Behandlung beim PFAPA-Syndrom bewerten. Darüber hinaus haben wir die demografischen und klinischen Merkmale von PFAPA-Patienten beschrieben.Materialen und Methoden Wir haben retrospektiv 58 PFAPA-Patienten analysiert, die zwischen Januar 2017 und Januar 2022 mit einer Colchicin-Behandlung begonnen hatten. Dabei wurden demografische Daten, klinische Merkmale, Labortests, genetische Analysen von Mutationen des Mittelmeerfiebers (MEFV) und Werte des Autoinflammatorischen Krankheitsaktivitätsindex (AIDAI) ausgewertet alle Patienten Darüber hinaus wurden die Patienten nach MEFV-Varianten in zwei Gruppen eingeteilt und verglichen.Ergebnisse Anfallshäufigkeit, -dauer und AIDAI-Scores sanken bei allen Patienten nach der Colchicin-Behandlung. Die Nachbeobachtungszeit betrug 13,53±6,65 Monate. Das mittlere±IQR-Alter bei der Diagnose betrug 3,2 (2–5) Jahre. Dreiunddreißig (56,9%) Patienten hatten heterozygote MEFV-Mutationen. Die häufigsten MEFV-Varianten waren M694V (63,6%). Es gab keinen signifikanten Unterschied zwischen den beiden Gruppen hinsichtlich der Colchicin-Reaktionen.Abschluss Die Behandlung mit Colchicin ist wirksam und sicher bei Patienten mit PFAPA, die häufig an Anfällen leiden. Es wurde kein Zusammenhang zwischen dem Vorhandensein heterozygoter MEFV-Mutationen und der Colchicin-Reaktion festgestellt.
Keywords: periodic fever; Colchicin; PFAPA syndrome; MEFV mutations